Appointment system design with interruptions and physician lateness - Klassen, Kenneth J.; Yoogalingam, Reena (International journal of operations & production management, 2013)
Purpose - Physician lateness and service interruptions are a significant problem in many health care environments but have received little attention in the literature. The purpose of this paper is to design appointment systems that reduce waiting times of the patient while maintaining utilization of the physician at a high level.Design methodology approach - Empirical data from time studies and surveys of medical professionals from multiple outpatient clinics are used to motivate the study. Simulation optimization is used to simultaneously account for uncertainty and to determine (near) optimal scheduling solutions.Findings - As lateness increases, it is shown that, in general, appointment slots should be shorter and pushed later in the session. Conversely, as interruptions rise, appointments in the middle of the session should be longer. These findings are fairly consistent over a variety of environmental conditions, including clinic sizes, service time variance, and costs of physician time compared to patients' time.Practical implications - This paper demonstrates that the dome plateau-dome scheduling patterns that have been found in prior studies work well under many of the new factors modeled here. This is encouraging because it suggests that a generalizable pattern is emerging in the literature for the range of environments studied in these papers and this research provides guidance as to how to adjust the pattern to account for the factors studied here. In addition, it is shown that some environments will perform better with a different pattern, which the authors denote a "descending step" pattern.Originality value - This paper differs from most prior studies in that the complexity of environmental variables and stochastic elements of the model are simultaneously accounted for by the simulation optimization algorithm. The (very few) prior papers that have used simulation optimization have not addressed the factors studied here.